Development of resilience of students in the educational process - Bielkina-Kovalchuk, Olena Vitaliivna (My University, 2024)
The article is devoted to the study of resilience in children. In recent years, social and economic instability in Ukraine, life during a pandemic, and military operations have placed high demands on human resources necessary for productive life and development. Therefore, modern research is aimed at studying the internal reserves of a person that help them survive even in problematic situations and overcome difficulties caused by stress. Childhood and adolescence is a period of rapid growth, enormous potential and, on the other hand, significant risks, when external factors have a powerful impact. On the one hand, the human psyche is vulnerable during this period, and on the other hand, it has enormous opportunities for development and formation of new abilities. In this regard, it is essential to study the peculiarities of resilience in children. Attention has been paid to the theoretical foundations of resilience development in the psychological and pedagogical literature, its age peculiarities and components, factors influencing the resilience of a personality in various life circumstances have been allocated and characterised. The empirical study has revealed the state of development of adolescent students' resilience. The obtained results have become the basis for the study of the educational environment of general secondary education institutions as a factor in the development of resilience. The organisational and pedagogical conditions for its development in students have been identified and theoretically substantiated.
Стаття присвячена дослідженням особливостей резильєнтності у дітей. В останні роки соціальна, економічна нестабільність в Україні, життя в умовах пандемії, військових дій висувають високі вимоги до людських ресурсів, необхідних для продуктивного життя та розвитку. Тому, сучасні дослідження вчених спрямовані на вивчення внутрішніх резервів людини, які допомагають їй виживати навіть у проблемних ситуаціях, долати труднощі, які зумовленні стресами. Дитячий і підлітковий вік є періодом стрімкого зростання, величезного потенціалу та, з іншого боку, значних ризиків, коли потужний вплив справляють зовнішні фактори. З одного боку, психіка людини в цей період є вразливою, з іншого – має величезні можливості розвитку та формування нових здібностей. У зв’язку з цим, є просто необхідним дослідження особливостей резильєнтності у дітей. Акцентовано увагу на теоретичних засадах розвитку резильєнтності у психолого-педагогічній літературі, виокремлено й схарактеризовано її вікові особливості та складники, чинники, що впливають на стійкість особистості у різноманітних життєвих обставинах. У результаті емпіричного дослідження було виявлено стан розвитку резильєнтності учнів підліткового віку. Отримані результати стали основою для дослідження освітнього середовища закладів загальної середньої освіти як чинника розвитку резильєнтності. Визначено та теоретично обґрунтовано організаційно-педагогічні умови її розвитку в учнів.
Keywords: соціальна робота; resilience; social work; резильєнтність; 373.091.212:159.922.7-044.332